YoutubeTM as an Information Source for Clinicians and Patients on Inlay-Onlay-Overlay Procedures - Kerem Can Işik; Handan Yildirim Işik (Atatürk University, 2024)
Objective: The aim of this study was to evaluate the quality of YouTubeTM videos on inlay, onlay, overlay restorations and to understand whether they were useful to patients and clinicians.Method: In the present study, "inlay, onlay and overlay" were used as keyword and YouTube videos was analyzed. The first 159 videos were analyzed by two independent researchers, and 69 were subsequently included in the study. The characteristics of the videos, target audience and source of uploaded were evaluated. A 15-point scale was used to classify videos into low and high content. Each video was evaluated for content quality using the Video Information and Quality Index (VIQI) and Global Quality Scale (GQS).Result: Most of the videos (44.9 %) had been uploaded by healthcare professionals, and followed by hospital/university (24.6 %). Definition of inlay-onlay-overlay was most mentioned topic. 63.8% of the videos was determined as low content and 36.2% high content. The VIQI and GQS scores of the high content group were significantly higher than low content group (P :.001; P